Safety Risk Management and Management Information Systems on Aviation Security Performance at Kualanamu International Airport - Nurhalimah Tusa’ Diah Siregar; Sugianto Sugianto; Nurbaiti Nurbaiti (Advances in Business & Industrial Marketing Research, 2026)
Purpose: The main focus of this study is to evaluate the extent to which the implementation of Safety Risk Management and Management Information System (MIS) affects the performance effectiveness of Avsec personnel at Kualanamu International Airport. Research Method: This study employed a quantitative survey approach, with primary data obtained through questionnaires distributed to 100 active Avsec personnel. The data were subsequently processed using Multiple Linear Regression analysis assisted by the SPSS statistical application. Results and Discussion: The results showed that Safety Risk Management and the Management Information System (MIS) had a significant positive effect on Avsec personnel's performance. These findings indicate that more optimal implementation of risk management and information systems leads to higher levels of personnel preparedness and effectiveness in maintaining aviation security. Implications: This study implies that airport management should strengthen safety risk management practices and optimize the implementation of an integrated management information system to improve Aviation Security performance. These findings provide practical insights for developing risk-based security strategies, improving personnel preparedness, and supporting more effective decision-making in airport security operations. Originality: The originality of this study lies in integrating Safety Risk Management and Management Information System as simultaneous determinants of Aviation Security Performance.